Legal Certainty of Implementing Telemedicine Services in Indonesia as Effort Towards Renewal of National Health Law - Mannas, Yussy Adelina; Elvandari, Siska (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 11 No 4 (2022), 2022)
Digital health services are carried out without direct interaction between doctors and patients, where patients only need to consult with doctors in virtual rooms, such as through electronic media and social media, known as Telemedicine. Apart from the hope that telemedicine promises various conveniences and opportunities so that it can be used as a solution in overcoming health problems, it is also realized that telemedicine brings potential legal problems in medical practice. Many of the legal implications of medicolegal telemedicine Other important aspects are the doctor-patient relationship, standard of care and informed consent. The formulation of the problem that will be raised in this study, namely: First, how is the legal certainty of the regulation of telemedicine services in terms of the laws and regulations in the field of health law in Indonesia? and Second, what is the concept of the right telemedicine regulation in the provision of health services based on the principle of legal certainty in Indonesia? The purpose of this research is to find out the legal certainty regarding the regulation of telemedicine services in Indonesia, and to find out the concept of the right telemedicine regulation based on the principle of legal certainty in Indonesia. The research method in writing this proposal uses a normative juridical approach. The result of this research is that legal certainty is needed to regulate telemedicine. There is no specific law that regulates telemedicine, and without legal certainty this will certainly have an impact on legal protection.